Comparative metabarcoding and biodiversity of gut-associated fungal assemblages of Dendroctonus species (Curculionidae: Scolytinae) - Pineda-Mendoza, Rosa María; Gutiérrez-Ávila, Jorge Luis; Salazar, Kevin F.; Rivera-Orduña, Flor N.; Davis, Thomas S.; Zúñiga, Gerardo (Frontiers in Microbiology, 2024)
The genus Dendroctonus is a Holartic taxon composed of 21 nominal species, some of these species are well known in the world as disturbance agents of forest ecosystems. Under bark of the host tree, these insects are involved in complex and dynamic associations with phoretic ectosymbiotic and endosymbiotic communities. Unlike filamentous fungi and bacteria, the ecological role of yeasts in the bark beetle holobiont is poorly understood, though yeast were the first group to be recorded as microbial symbiont of these beetles. We metabarcode ITS2 to characterize and compare the gut fungal assemblages associated to 14 species of Dendroctonus. A total of 615,542 sequences were recovered yielding 248 fungal amplicons sequences variants (ASVs). Fungal diversity was represented by 4 phyla, 16 classes, and 34 orders, 54 families, and 71 genera with different relative abundances among Dendroctonus species. a-diversity consisted of 32 genera of yeasts and 39 genera of filamentous fungi. Analysis of b-diversity indicated differences in the composition of the gut fungal assemblages among bark beetle species, with differences in the species and phylogenetic diversity. A common core mycobiome was recognized at the genus level, integrated mainly by Candida present in all bark beetles, Nakazawaea, Cladosporium, Ogataea, and Yamadazyma. The bipartite networks confirm that these fungal genera show a strong association between beetle species and dominant fungi, which are key to maintain the structure and stability of the fungal community. The functional variation in the trophic structure was identified among libraries and species, with Pathotroph-Saprotroph-Symbiotroph represented at the highest frequency, followed by Saprotroph-Symbiotroph, and lastly Saprotroph only. The overall network suggests that yeast and fungal ASVs in the gut of these beetles show positive and negative associations among them. This study, outline a micobiome associated with Dendroctonus nutrition and provide a starting point for future in vitro and omics approaches addressing potential ecological functions and interactions among fungal assemblages and beetle hosts.